Divergence among mother trees of Handroanthus serratifolius (Vahl) S. O. Grose regarding seed quality traits - da Cruz Silva, Patrícia Cândido [UNESP]; Zanatto, Bruna [UNESP]; de Paula, Rinaldo Cesar [UNESP] (GN1 Sistemas e Publicacoes, 2023)
Environmental infl uences and genetic variability can promote, within the same species, variations between plants with intrinsic traits to the seeds. This work aimed at investigating the divergence among Handroanthus serratifolius mother trees from traits related to the physiological quality of seeds. Seeds collected from 13 mother trees were submitted to tests germination, electrical conductivity (EC), cold, controlled deterioration, and accelerated aging. Five replications of 50 and 25 seeds each were used for the cold test and other tests, respectively. The average data per mother tree were submitted to cluster analysis by the methods of Ward, k-means, and Principal Component Analysis (PCA). The mother trees were grouped into 4 clusters by the Ward’s and K-means methods, and confi rmed by the PCA, but with varying cluster compositions. Cluster 2 grouped the mother trees with lower seed quality as demonstrated by the lowest values for most of the evaluated traits, but the highest EC and the second-highest value for the germination uncertainty index. On the other hand, cluster 4 grouped the mother trees with better seed quality. Of the 22 evaluated traits, eight are probably suitable for discarding due to their little contribution to the original variability. The results of the different clustering methods indicate signifi cant differences between the mother trees regarding the physiological quality of seeds, showing that these parameters may be used to guide breeding programs aiming to produce high-quality seeds and seedlings of H. serratifolius.
Divergência entre árvores matrizes de Handroanthus serratifolius (Vahl) S. O. Grose quanto a caracteres de qualidade de sementes
Keywords: Cluster analysis; Native species; Vigor